Pelatihan Kewirausahaan pada Masyarakat di Desa Lalowulo Kecamatan Besulutu Kabupaten Konawe - Tanzil; Juhaepa; Peribadi; La Ode Monto Bauto; Sarpin (Indonesian Journal of Community Services, 2022)
The purpose of this community service activity is to conduct entrepreneurship training in the community to encourage people to have an independent life. This service activity was carried out in Lalowulo Village, Besulutu District, Konawe Regency. The implementation of this devotion is carried out in two stages; First counseling/training. In the first stage, the extension worker gives a lecture to the trainees. Extension workers/trainers encourage all participants to have high motivation for entrepreneurship. Furthermore, extension workers/training interact directly with citizenship to understand the problems faced in entrepreneurship. This service activity also utilizes the Focus Group Discussions method with various parties, especially with the local government, and business actors. This activity has also provided guidance to business groups in the community. The group of business groups is encouraged and trained to take advantage of the opportunities that exist to obtain the greatest profit. This activity is integrated with the Village Development Program in the area of service activities so that there is mutual support between the community and the Village Government.